Obtenção de biocimento de fosfato de cálcio para aplicação como dispositivo de liberação de fármaco - Silva, Suely Alves (2018)
One of the major challenges of science in recent years has been the development of technologies for the production of vehicles (or carriers) that allow the controlled release of drugs in the human body, making it possible to reduce the doses of medicines, making them at the same time more effective. One way to make rational and effective use of drugs is precisely their local and controlled administration. In this study, β-TCP was synthesized by solid state reaction, with the main objective of producing a biocement to evaluate the incorporation and release of the drug Indomethacin, which is an anti-inflammatory. β-TCP was characterized by X-ray Diffraction (XRD), Infrared Spectroscopy (IR), Scanning Electron Microscopy with Energy Dispersion X-Ray Spectroscopy (SEM) and determination of particle size distribution (BET). The cytotoxicity test was also carried out following ISO 10993-5 and ISO 10993-12 standards. The biocement was characterized by XRD, MEV, Determination of hydrogenion potential (pH), apparent porosity, Pick Time and diametral compression resistance. After the incorporation and release of the drug Indomethacin in the biocement, the study of the release, the setting time, the resistance to diametral compression and the ANOVA statistical analysis of the results were carried out. The characterization carried out showed that the solid phase reaction of calcium hydroxide and calcium hydrogen phosphate allows the preparation of monophasic β-TCP, provided that the appropriate combination of the synthesis parameters is used. Therefore, the obtained material has no toxicity, is biocompatible and shows a strong candidate for biomedical applications.